All Three Endogenous Quinone Species of Escherichia coli Are Involved in Controlling the Activity of the Aerobic/Anaerobic Response Regulator ArcA - van Beilen, Johan W. A.; Hellingwerf, Klaas J. (Frontiers in Microbiology, 2016)
The enteron Escherichia coli is equipped with a branched electron transfer chain that mediates chemiosmotic electron transfer, that drives ATP synthesis. The components of this electron transfer chain couple the oxidation of available electron donors from cellular metabolism (e.g., NADH, succinate, lactate, formate, etc.) to the reduction of electron acceptors like oxygen, nitrate, fumarate, di-methyl-sulfoxide, etc. Three different quinones, i.e., ubiquinone, demethyl-menaquinone and menaquinone, couple the transfer of electrons between the dehydrogenases and reductases/oxidases that constitute this electron transfer chain, whereas, the two-component regulation system ArcB/A regulates gene expression, to allow the organism to adapt itself to the ambient conditions of available electron donors and acceptors. Here, we report that E. coli can grow and adjust well to transitions in the availability of oxygen, with any of the three quinones as its single quinone. In all three ‘single-quinone’ E. coli strains transitions in the activity of ArcB are observed, as evidenced by changes in the level of phosphorylation of the response regulator ArcA, upon depletion/readmission of oxygen. These results lead us to conclude that all quinol species of E. coli can reduce (i.e., activate) the sensor ArcB and all three quinones oxidize (i.e., de-activate) it. These results also confirm our earlier conclusion that demethyl-menaquinone can function in aerobic respiration.